Audit of bone marrow trephines. - Bishop, P W (1992)
AIMS: To establish criteria of adequacy for bone marrow trephine biopsy specimens and to audit the quality of trephines performed at the Christie Hospital, Manchester. METHODS: Trephines (n = 767) performed over 12 months were reviewed. Their lengths, and the lengths of their constituent parts (soft tissue, cortex, crushed marrow and interpretable marrow) were measured. The mean performance of each operator was calculated. Criteria of adequacy were established by a review of the published findings and an analysis of the relation between trephine length and the rate of infiltration by tumour. RESULTS: Before processing, the average trephine was 1.59 cm long. Trephines shrunk by 25% during processing. In histological sections the average length was 1.15 cm, consisting of 0.09 cm of soft tissue, 0.04 cm of cortex, 0.26 cm of disrupted marrow and 0.74 cm of interpretable marrow. A large number of operators were taking trephine biopsy specimens and their performance varied considerably. Review of the published findings suggested that the minimum adequate length is in the range 1.5 cm to 2.0 cm. The analysis of the relation between length of trephine and the rate of positivity for neoplasia yielded a minimum adequate length of 1.2 cm in section (1.6 cm before processing). Fifty eight per cent of the trephines were inadequate by this criterion. There was a tendency for the Jamshidi needle to produce a longer trephine than the Islam needle. CONCLUSION: According to objective criteria, at the Christie Hospital, many operators are producing a high proportion of inadequate bone marrow trephines.